PLA2-R positive primary membranous nephropathy: a case report - Quen Sánchez, Eduardo Abraham; Ortiz Castañeda, Carlos Eduardo; Anaya Zamora, Juan Carlos; Baeza Hernández, Yari Esilde; Dzul Caballero, José Emmanuel (International Journal of Research in Medical Sciences, 2025)
Membranous nephropathy (MN) is a significant cause of nephrotic syndrome in adults, often linked to the presence of circulating antibodies against phospholipase A2 receptor (PLA2R). This case report details the clinical presentation, diagnostic process, treatment, and outcomes of a patient diagnosed with PLA2R-positive membranous nephropathy. The report highlights the importance of early diagnosis and personalized treatment strategies, demonstrating the evolving landscape of MN management. A brief review of the literature related to the topic is also presented. For this purpose, a search was made in freely accessible sources, selecting those with the most relevant and up-to-date information.